Copper-Catalyzed Reactions of Aryl Halides with N-Nucleophiles and Their Possible Application for Degradation of Halogenated Aromatic Contaminants - Weidlich, Tomáš; Špryncová, Martina; Čegan, Alexander (MDPI, 2022)
This review summarizes recent applications of copper or copper-based compounds as a nonprecious metal catalyst in N-nucleophiles-based dehalogenation (DH) reactions of halogenated aromatic compounds (Ar-Xs). Cu-catalyzed DH enables the production of corresponding nonhalogenated aromatic products (Ar-Nu), which are much more biodegradable and can be mineralized during aerobic wastewater treatment or which are principally further applicable. Based on available knowledge, the developed Cu-based DH methods enable the utilization of amines for effective cleavage of aryl-halogen bonds in organic solvents or even in an aqueous solution.
Mědí katalyzované reakce arylhalogenidů s N-nukleofily a jejich možná aplikace pro degradaci halogenovaných aromatických kontaminantů
Keywords: amine; amination; arylation; halogenated aromatic compounds; aryl halide; dehalogenation; C-N cross-coupling; amin; aminace; arylace; halogenované aromatické sloučeniny; arylhalogenid; dehalogenace; C-N křížová vazba